Temporal Trends in Strut‐Level Optical Coherence Tomography Evaluation of Coronary Stent Coverage: A Systematic Review and Meta‐Analysis. Issue 7 (28th December 2015) - Lee, Kwan S.; Lee, Justin Z.; Hsu, Chiu‐Hsieh; Husnain, Muhammad; Riaz, Haris; Riaz, Irbaz Bin; Thai, Hoang; Cassese, Salvatore; Finn, Aloke; Samady, Habib; Byrne, Robert A.
Abstract : Objectives: We sought to pool data from all studies with reported strut‐level data in human subjects evaluated by optical coherence tomography (OCT) surveillance and to compare the aggregate data of stent strut coverage on a longitudinal temporal timeline from initial implantation for different coronary stent subtypes. Background: Delayed strut coverage following drug‐eluting stent (DES) implantation is an important contributor to late stent thrombosis (LST). OCT can detect stent strut coverage. Methods: We conducted a systematic search of published or presented studies reporting OCT stent strut coverage of bare‐metal stents (BMS) and DES in PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials to June 2014. Data from 3, 515 patients with strut‐level data on 731, 761 struts were analyzed. Results: The temporal kinetics of strut coverage differed according to stent type. The rate of strut coverage, reflected by the calculated regression coefficient, was found to be the highest in BMS, followed by early generation zotarolimus‐eluting stent, everolimus‐eluting stent, newer‐generation zotarolimus‐eluting stent, paclitaxel‐eluting stent, and sirolimus‐eluting stent ( p  < 0.0001). Conclusions: Aggregate rates of stent strut coverage assessed by OCT surveillance differed according to stent type. The clinical implications of these differences require further study but may underlie the differences in rates of stent thrombosis observed in clinical trials with different stent types. © 2015 Wiley Periodicals, Inc.